The role of initial shares in multi-period production economies with incomplete markets - Egbert Dierker (Institute for Advanced Studies (IHS), 2017)
This paper focuses on a single firm with constant returns to scale in a multi-period setting with incomplete markets and a single good per state. Profits vanish whenever the firm maximizes profits with respect to a given price system. The paper addresses the following question: Shall the firm always act as a price taker? In the case of a partnership, there are no initial shares and no profits accrue from production. A corporation, however, has initial shareholders and can sell its output at any price. An example shows that this additional freedom can improve efficiency and welfare. This results from the fact that a wedge between price and cost can mitigate the inefficiency caused by the consumers who disregard the impact of their initial portfolio decisions on subsequent markets.
Keywords: D21; D52; D61; 330; multi-period economies with incomplete markets; partnerships and corporations; competitive price perceptions; the role of initial shares; the objective of a firm; efficiency and social welfare